SOCIAL DISTANCING: INDONESIAN POLICY REPONSE TO THE CORONA VIRUS DISEASE 2019 (COVID-19) - Herdiana, Dian (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2020)
Coronavirus becomes a pandemic disease faced by more than two hundred countries that impacts multi-dimensional aspects, the various policy is carried out as an effort to tackle the coronavirus, it is polarized into 2 (two) policy, namely lockdown and social distancing. Indonesia as a country infected by the coronavirus does the same thing, but empirically the policy taken is debated. On the one hand, the central government sets social distancing policy, on the other hand, some regional governments set local-scale lockdown policy. This article uses a qualitative approach with a descriptive analysis method, the data sources in this study are based on two sources both the primary data obtained through focused observations in the Bandung City and literature studies of various documents that relevant to the coronavirus topic. The results revealed that the driving factors.The inhibiting factors in the implementation of social distancing policy consist of 3 (three), namely: First, the capacity of the organization both at the central government level and the regional government level. Second, the different strategies implemented by the government in which the central government implements a social distancing policy strategy, while the regional governments implement a lockdown policy strategy. Third, community obedience where there are still many people who violate social distancing policy.Keywords: Coronavirus, COVID-19, lockdown, social distancing, policy